Frequency and significance of IgG4 immunohistochemical staining in liver explants from patients with primary sclerosing cholangitis. Issue 3 (18th April 2014) - Fischer, Sandra; Trivedi, Palak J.; Ward, Stephen; Greig, Paul D.; Therapondos, George; Hirschfield, Gideon M.
Summary Dense tissue infiltrates of IgG4+ plasma cells >50/high‐powered field (HPF) are purportedly highly specific for IgG4‐related disease. However, the frequency and significance of liver‐infiltrating IgG4+ plasma cells in primary sclerosing cholangitis (PSC) applying these cut‐offs has not been determined. We sought to determine the incidence of intrahepatic IgG4‐positive staining in PSC patients undergoing transplantation, correlating findings with clinical parameters. Immunohistochemical staining was performed on liver explants obtained between 1991 and 2009. Of 122 explants obtained, hilar IgG4+ staining was found to be mild (10–29 IgG4+ cells/HPF) in 23.0%, moderate (30–50/HPF) in 9.0% and marked (>50/HPF) in 15.6%. Marked hilar lymphoplasmacytic infiltration was significantly associated with marked hilar IgG4+ staining (P < 0.001). No patient had marked peripheral IgG4+ staining, although mild and moderate staining was observed in 24.5% and 3.3% respectively. Marked hilar IgG4+ staining was significantly associated with the presence of dominant biliary strictures (P = 0.01) and need for biliary stenting (P = 0.001). There did not, however, exist any significant differences in the age at PSC diagnosis, presence of inflammatory bowel disease or extrahepatic autoimmune disease, frequency of cholangiocarcinoma, interval between diagnosis and transplantation, or post‐transplant PSC recurrence or survival. Of 51 control liver sections (PBC = 18; HCV = 19; HBV = 8; AIH = 6), none had marked or moderate hilar IgG4+ staining, whereas mild staining was seen in only 10% (P < 0.001). Marked (>50/HPF) hilar IgG4+ lymphoplasmacytic infiltration is frequently observed in PSC and associated with the presence of dominant biliary strictures. However, unlike serum IgG4+, this does not seemingly associate with clinical disease course.